A Postcolonial Reading of Memory in Malouf’s Remembering Babylon (1993) - DERMACH, Meriem Bochra; SELT, Djihad Afaf (Faculty of Letters and Foreign Languages Department of English, 2018)
This dissertation aims at providing a postcolonial reading of memory in David Malouf’s Remembering Babylon (1993). Through the use of a theoretical background on the theory chosen, some postcolonial key concepts were examined in the novel, these concepts are identity, hegemony, and hybridity. In addition to the examination of the role memory plays in the novel. Since the aim is analyzing the novel, the approach adopted was the analytical approach. The study resulted in proving that the novel contains a set of postcolonial key concepts. Memory was also found of a major role, through showing that because of Gemmy’s inability to remember and use his English language, Gemmy, the protagonist of the story, presents a confusing figure, which made suspicion grow among the white community that he came to. Neither Gemmy nor the white settlers could identify to whom does he belong. Being in such a situation is a result of the differences and lack of integration between the white settlers and the aborigines in Australia. Language was also found an important theme in the novel in relation to identity, hegemony, as well as to memory